Linguistic and pragmatic skills in toddlers with cochlear implant. Issue 6 (29th July 2013) - Rinaldi, Pasquale; Baruffaldi, Francesca; Burdo, Sandro; Caselli, Maria Cristina
Abstract: Background: An increasing number of deaf children received cochlear implants (CI) in the first years of life, but no study has focused on linguistic and pragmatic skills in children with CI younger than 3 years of age. Aims: To estimate the percentage of children who had received a CI before 2 years of age whose linguistic skills were within the normal range; to compare linguistic skills of children implanted by 12 months of age with children implanted between 13 and 26 months of age; and to describe the relationship among lexical, grammar and pragmatic skills. Methods & Procedures: The participants consisted of children who were included on the patient lists of the Service of Audio‐Vestibology of the Circolo Hospital in Varese, Italy, and met the following criteria: chronological age between 18 and 36 months; CI activated between 8 and 30 months of age; absence of other reported deficits; hearing parents; and not less than 6 months of CI experience. Language development was evaluated through MacArthur–Bates CDI; pragmatic skills (assertiveness and responsiveness) were evaluated through the Social Conversational Skills Rating Scale. The scores obtained were transformed into z ‐scores and compared with normative data. The relationship among lexical, grammar and pragmatic skills were tested using Spearman Rho correlations. Children with CI were divided into groups based on the age at CI activation and the differences between the two groups were tested using the Student's t ‐test. Outcomes & Results: Data from 23 deaf children were collected. Fewer than half of the children were within the normal range for lexical production and use of sentences; more than one‐third of them fell below the normal range for both lexical and grammar skills. No significant difference was found in vocabulary size or early grammar skills when comparing children who received the CI by 12 months of age with those implanted during the second year of life. Despite the strong relationship among lexical, grammar and pragmatic skills, the delays found for grammar and pragmatic skills were greater than expected based on the vocabulary size. Age at diagnosis of hearing loss was the only predictor of vocabulary size. Conclusions & Implications: CI may provide deaf children with a good opportunity to develop language skills, but severe difficulties in early social experiences and interaction mediated by language still remain. Delays in these aspects suggest that interventions improving pragmatic skills are recommended even on very young children with CI.